Brincar, criar e construir : a potência do encontro entre as crianças e os objetos descartados na Educação Infantil - Godinho, Vicente Rosa (Universidade Federal de São Carlos, 2024)
Children establish a playful and inventive relationship with the world. Various objects we discard daily, either at home or in industries, carry potential and possibilities. With that in mind, this research was conducted with the proposal of promoting an encounter among three groups of children, aged between 4 and 5 years old, from a Children’s Educational Center (in Sorocaba/SP). This educational center has discarded materials such as cardboard boxes, tubes, jars, lids, spools, bottles, pipes, and wood scraps, among others. The aim was to observe and register this playful and creative process that children with access to these materials go through, and also how they use these elements, what they do, and what the possibilities are for transformations and creations of these objects, as well as defending children’s rights to school plays at Early Childhood Education. Here are some questions that mobilized and guided the research: What relationships do children establish with these elements in their playful and inventive explorations? In what way, do these elements enrich and enhance their play and creations? Can playing with discarded objects favor the central role of children and their sense of authorship? This is a qualitative research study using a methodology known as “invite-research”, which consists of creating and organizing spaces using visual compositions with various types of discarded objects of different shapes, sizes, colors, and materials, creating an inspiring visual aesthetic that invites and provokes children to play and explore the possibilities of using these objects. While the children were playing, photographic records were made of their playful relationship with the discarded objects. The images are used as visual narratives that testify to the children's play and inventive processes, as well as act as catalysts for thought and provoke numerous reflections. The theoretical discussions are carried out based on an epistemological bricolage with various thinkers such as Huizinga, Benjamin, Bachelard, Lapoujade, among others. As a result, this research revealed the children's inventive and imaginative potential and their ability to perceive the potentiality and virtuality of discarded objects. These objects acted as triggers and catalysts of imagination while being transformed into language through the children's numerous creations, constructions, visual compositions, and many experimentations. Considering that these objects have no particular value or utility, the children were able to exercise their authorship and inventiveness, determining new uses and meanings for these objects, and transforming them into rich toys and powerful elements for their play. In this way, the research confirmed the importance of promoting open proposals in early childhood education. These proposals should support the interests and needs of the children, allowing them to exercise their inventive and imaginative potential through their play, creations, and experimentation. It also points out the power of play as a creator of territories of experimentation and creation - actions that enable children to act and express themselves in the world, inspiring and educating adults.
Playing, creating, and building: the power of the encounter between children and discarded objects in Early Childhood Education
Keywords: Educação Infantil; Crianças; Brincar; Objetos descartados; Invenção; Brinquedo; Early Childhood Education; Children; Play; Discarded objects; Invention; Toy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO